2023
DOI: 10.2147/ijn.s411819
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Apoptotic Extracellular Vesicles from Adipose Tissue and Their Efficacy in Promoting High-Quality Skin Wound Healing

Abstract: A lot of strategies have been attempted to achieve high-quality skin wound healing, among them, fat transplantation has been used for skin wound repair and scar management and has shown beneficial effects. However, the underlying mechanism is still unclear. Recently, studies found that transplanted cells underwent apoptosis within a short period and apoptotic extracellular vesicles (ApoEVs) might play the therapeutic role. Methods: In this study, we directly isolated apoptotic extracellular vesicles from adipo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 49 publications
0
9
0
Order By: Relevance
“…Specifically, the activated MSCs exhibit migratory behavior along blood vessels, translocate across the vascular endothelial cells (vECs) and migrate into the damaged tissues . Moreover, the recruitment of MSCs toward injured femurs mainly relies on adhesion, while the adhesive interaction between MSCs and blood vessels was dependent on the binding between VLA-4 on MSCs and VCAM1 on vECs. , Besides that, recent studies have shown that ApoEVs could be endocytosed by multiple types of cells, such as macrophages, dendritic cells, epithelial cells, fibroblasts, and endothelial cells, etc., which mediated the intercellular communication, and altered the cellular behaviors of recipient cells. To explore whether the ApoEV could enhance MSC recruitment through the interaction between MSCs and blood vessels, the mCherry-labeled MSCs (mCherry-MSCs) were intravenously injected after the femoral defect fabrication (Figure A).…”
Section: Resultsmentioning
confidence: 99%
“…Specifically, the activated MSCs exhibit migratory behavior along blood vessels, translocate across the vascular endothelial cells (vECs) and migrate into the damaged tissues . Moreover, the recruitment of MSCs toward injured femurs mainly relies on adhesion, while the adhesive interaction between MSCs and blood vessels was dependent on the binding between VLA-4 on MSCs and VCAM1 on vECs. , Besides that, recent studies have shown that ApoEVs could be endocytosed by multiple types of cells, such as macrophages, dendritic cells, epithelial cells, fibroblasts, and endothelial cells, etc., which mediated the intercellular communication, and altered the cellular behaviors of recipient cells. To explore whether the ApoEV could enhance MSC recruitment through the interaction between MSCs and blood vessels, the mCherry-labeled MSCs (mCherry-MSCs) were intravenously injected after the femoral defect fabrication (Figure A).…”
Section: Resultsmentioning
confidence: 99%
“…60,61 Previous studies found adipose tissue-derived ApoEVs could directly increase the ratio of type III to type I collagen in fibroblasts and promote skin wound healing. 25 The effects of HUVECs-derived ApoEVs on fibroblasts were investigated in this study. In vitro experiments revealed that ApoEVs could slightly promote the proliferation and migration of fibroblasts.…”
Section: Discussionmentioning
confidence: 99%
“…14,15 Previous studies have primarily utilized bone marrow mesenchymal stem cells (BMSCs) 13,[16][17][18][19][20][21][22] as the source of ApoEVs. Other cell types, including adipose mesenchymal stem cells (ASCs), 18 embryonic mesenchymal stem cells (ESCs), 23 umbilical cord mesenchymal stem cells (UMSCs), 23 and deciduous pulp stem cells, 24 as well as whole adipose tissue, 25 have also been selected in various studies. Among them, ApoEVs, isolated from BMSCs 22 and deciduous pulp stem cells, 24 were reported to regulate endothelial cell behavior and promote angiogenesis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, emerging studies have demonstrated that apoVs derived from MSCs (MSC-apoVs) contribute to MSC-mediated therapeutic e cacy [15][16][17] . Moreover, the direct application of MSC-apoVs shows therapeutic potential in a variety of diseases [18][19][20][21][22][23][24][25] . In line with these reports, our previous studies have determined the effective functions of MSC-apoVs in the treatment of bone loss 26 , wound healing 27 , hemophilia A 28 , type 2 diabetes 29 , multiple myeloma 30 , traumatic hemorrhage 31 , arthritis 32 , etc.…”
Section: Introductionmentioning
confidence: 99%